IMPLEMENTASI PROGRAM HIBAH AIR MINUM 2024 DI PERUMDA TUGU TIRTA KOTA MALANG - Farida Rahmawati; Diana Fitriani; Chatryne Marthadivea V G; Christabel Owena Yanuar (Journal Publicuho, 2023)
This study aims to find out how the process of implementing the drinking water grant program is and to analyze the success factors and obstacles in overcoming the availability of drinking water for Low-Income Communities (MBR). In this study, researchers used descriptive research with a qualitative approach. Primary and secondary data sources. Then the data were analyzed interactively in the opinion of Miles Huberman and Saldana (2014). The results of the research show that the implementation of this program starts in 2021 until 2023. As of February 27, 2023, 1,083 SRs have been installed and according to the commitment of Perumda Air Drinking Tugu Tirta Malang City will install all house connections that have already paid a new installation fee. Suggestions from researchers to Perumda Drinking Water Tugu Tirta Malang City so that the obstacles encountered in the process of working on this program for the community can be reviewed and used as evaluation material so that in the future service to the community can be better.